English Teachers’ Assessment Literacy in Tabanan, Bali, Indonesia - Gusti Ayu Bintang Purwani; A.A. Gede Yudha Paramartha; Luh Gede Eka Wahyuni (Pascasarjana Universitas Negeri Makassar, 2022)
Assessment become one of the essential part in the process of teaching and learning. The influence of good assessment practices may affect the students learning outcomes. The goal of this study was to find out how well English teachers in Tabanan, Bali, Indonesia were assessment literate. This research used a descriptive quantitative method which utilized purposive random sampling technique in determining the sample of this study. In obtaining the data, teachers’ assessment literacy questionnaire were used which contains 30 questions related to teachers’ assessment practices. Then, the data were analyzed using ideal mean score to determine the teacher assessment literacy level of each teacher. The result indicates that the level of English teachers’ assessment literacy in Tabanan regency was categorized as ‘fair’. In which, there were 44.4% English teachers got the ‘fair level, and 40% teachers in the level of ‘good’ out of 45 teachers who contribute to fill out the teacher assessment literacy questionnaire. Therefore, more efforts, willingness, and more practices to be able to improve the assessment literacy level of English teachers.